CHANGES IN HUMAN AESTHETIC TASTE IN THE POSTMODERN ERA - Kаkhоrоv Рulоtjоn Khursаnmurоdоvich (Journal Park Publishing, 2025)
In the postmodern era, aesthetic consciousness and human taste have undergone profound transformation. Rapid technological development, global communication, and the expansion of virtual space have redefined aesthetic values and blurred the boundaries between beauty and ugliness, art and life. This study provides a philosophical analysis of postmodern aesthetic concepts, examining social, informational, and cultural factors influencing the evolution of human taste and revealing new dimensions of aesthetic perception and spiritual orientation in contemporary society.
Keywords: Postmodernism, aesthetics, aesthetic taste, values, transformation, culture, individualism, technology, media aesthetics, thinking.